Ischemic Stroke in Patients With Hypertrophic Cardiomyopathy According to Presence or Absence of Atrial Fibrillation. Issue 2 (4th October 2021) - Fauchier, Laurent; Bisson, Arnaud; Bodin, Alexandre; Herbert, Julien; Spiesser, Pascal; Pierre, Bertrand; Clementy, Nicolas; Bernard, Anne; Babuty, Dominique; Lip, Gregory Y.H.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Patients with hypertrophic cardiomyopathy (HCM) have high risk of ischemic stroke (IS), especially if atrial fibrillation (AF) is present. Improvements in risk stratification are needed to help identify those patients with HCM at higher risk of stroke, whether AF is present or not. Methods: This French longitudinal cohort study from the database covering hospital care from 2010 to 2019 analyzed adults hospitalized with isolated HCM. A logistic regression model was used to construct a French HCM score, which was compared with the HCM Risk-CVA and CHA2 DS2 -VASc scores using c-indexes and calibration analysis. Results: In 32 206 patients with isolated HCM, 12 498 (38.8%) had AF, and 2489 (7.7%) sustained an IS during follow-up. AF in patients with HCM was independently associated with a higher risk for death (hazard ratio, 1.129 [95% CI, 1.088–1.172]), cardiovascular death (hazard ratio, 1.254 [95% CI, 1.177–1.337]), IS (hazard ratio, 1.210 [95% CI, 1.111–1.317]), and other major cardiovascular events. Independent predictors of IS in HCM were older age, heart failure, AF, prior IS, smoking and poor nutrition (all P <0.05). For the HCM Risk-CVA score, CHA2 DS2 -VASc score and a French HCM score, all c-indexes were 0.65 to 0.70, with good calibration. Among patients with AF, the CHA2 DS2 -VASc score had marginal improvement over the HCM Risk-CVA score but was less predictive compared with the French HCM score ( P =0.001). In patients without AF, both HCM Risk-CVA score and the French HCM score had significantly better prediction compared with CHA2 DS2 -VASc (both P <0.0001). Decision curve analysis demonstrated that the French HCM score had the best clinical usefulness of the 3 tested risk scores. Conclusions: Patients with HCM have a high prevalence of AF and a significant risk of IS, and the presence of AF in patients with HCM was independently associated with worse outcomes. A simple French HCM score shows good prediction of IS in patients with HCM and clinical usefulness, with good calibration.